SOLVING THE STUDENTS’ PROBLEMS IN WRITING ARGUMENTATIVE ESSAY THROUGH COLLABORATIVE WRITING STRATEGY - M. Fadhly Farhy Abbas; Herdi Herdi (University of Kuningan, 2018)
This research is based on the students’ problems in writing argumentative essay, especially in developing and organizing ideas, using good grammar and diction, and applying correct writing mechanics, such as the use of capital letter, spelling, and punctuation. The purpose of this research is to solve the students’ problems in writing argumentative essay through collaborative writing strategy. The design employed in this research was classroom action research. The participants involved in this research were 23 students of English Education Department, Faculty of Teacher Training and Education, University of Lancang Kuning Pekanbaru, Indonesia. The instruments used in this research were writing test, field note, observation checklist, and interview. Based on the result of the test, the students’ score had reached the criteria of success set, and it was significantly improved from the result before the research conducted. The mean score of the mid-term test was 54.9, and the mean score of the cycle test was 74.3. In addition, based on the data gained from the field note, observation checklist, and interview, it was found that the students were active, creative, and enjoy the learning process. In conclusion, the use of collaborative writing strategy can solve the students’ problems in writing argumentative essay as well.Keywords: writing skill; writing aspects; argumentative essay; collaborative writing strategy; classroom action research.